Evaluation of the effects on SpO2 of N95 mask (FFP2) on dental health care providers: a cross-sectional observational study - Sabina Saccomanno; Rebecca Jewel Manenti; Silvia Giancaspro; Licia Coceani Paskay; Christine Sofiane Katzenmaier; Rodolfo Francesco Mastrapasqua; Vincenzo Quinzi (BMC, 2022)
Abstract Objective The purpose of this cross-sectional observational study was to evaluate the effects of SpO2 in a sample of dental health care providers who wear a N95 mask or Filtering Face Piece (FFP2) for four consecutive hours, measured by a pulse oximeter before donning the mask and again after four hours of work and to offer some strategies to minimize discomfort and improve communication with their patients while wearing the mask. Materials and methods A 17-item questionnaire was sent via Google Drive to various practitioners in Italy and the USA. A sample of 162 questionnaires were returned from dentists, orthodontists, dental hygienists and dental assistants who committed to wearing a FFP2 for 4 consecutive hours during a work day and then measuring the oxygen saturation by way of a pulse oximeter before and after the 4 working hours. The final analysis was performer on 147 viable questionnaires returned. The sample was composed of 62 males and 85 females with an average age of 42.9 ± 12.0 years. Results For the entire sample population, the baseline saturation was 98.6 ± 1.2 and, after four hours of mask wearing, there was a significant decrease in oxygen saturation to 97.0 ± 2.9 (p < 0.01). No statistical differences in SpO2 were found across specialties or across types of procedures performed during the 4 h. Heart rates were not significantly different before and after the 4 h in all categories. The 3 most frequent reported complaints were: fatigue (64%), headache (36%) and external ear pain (31%). The most common additional personal protective equipment (PPE) was a mask shield (78%) and those who wore the mask continuously reported more communication difficulty with patients, compared with those who took the mask off more often, in fact, 64% of the subjects reported that using the mask influenced their communication with their patients. Based on the results of the questionnaire, a list of breathing and vocal folds health strategies was devised and proposed, along with strategies to augment communication with patients. Conclusions This study highlights a significant decrease in oxygen saturation after only 4 h of work (except for smokers) while wearing a FFP2, and confirms the widespread symptoms of fatigue, headache and pain behind the ears that dental professionals experience. But it also highlighted how mask wearing impaired communication with patients and wearing additional masks and a facial shield may add to those communications difficulties. This aspect and the need for better communication can lead the operators to remove the mask to improve breathing and communication, thus putting themselves at a risk of infection. Of all the aspects explored in this study, the most interesting was indeed the impact on fatigue and communication and the strategies proposed in this article can easily be implemented to reduce headache and fatigue by improving breathing efficiency and by aiding communication while donning a mask by improving voice quality and by using augmentative communication tools.